Emerging hormonal agents for the treatment of prostate cancer. (3rd July 2022) - Bochner, Emily; Gold, Sam; Raj, Ganesh V.
ABSTRACT: Introduction: Prostate cancer is the most common solid organ malignancy in men in the United States. Until recently, treatment options for men with metastatic disease were limited and patients faced poor outcomes with minimal alternatives. The landscape of prostate cancer treatment has transformed and taken shape over the last 20 years with novel hormonal and non-hormonal therapeutics that have demonstrated significant improvement in survival. However, patients with advanced disease still face imminent progression on hormone blockade therapy. Areas covered: There is a significant market opportunity to devise novel, more potent agents for patients with hormone-resistant disease. Here we review the existing treatment options in men with advanced prostate cancer, the market opportunity within this field, goals of current research, and the novel agents under investigation, including androgen receptor degraders, testosterone synthesis pathway inhibitors, DNA-binding domain and N-terminal domain antagonists, and the combination of hormonal and non-hormonal agents. Expert opinion: Combination therapy regimens and novel agents targeting alternative binding domains of the androgen receptor are of great interest, as they may overcome resistance mechanisms and hold promise as the future of advanced prostate cancer treatment.